Laser directed energy deposition of heteroarchitected Ti6Al4V composites: In-situ TiB/TiC network engineering for multi-mechanistic strength-ductility synergy - Shenghao Hu; Chengfang Chai; Shuai Guo; Fengxian Li; Yichun Liu; Jianhong Yi; Jie Yu; Jürgen Eckert (Journal of Materials Research and Technology)
Achieving an optimal balance between strength and ductility in titanium matrix composites (TMCs) remains a critical challenge. This study presents a novel approach to fabricate heterostructure (TiB + TiC)/Ti6Al4V composites via laser-directed energy deposition (LDED) with B4C-derived in-situ reinforcement. High-energy laser irradiation triggers an in-situ reaction between nano-B4C and Ti6Al4V, forming a three-dimensional network of rod-like TiB whiskers and equiaxed TiC nanoparticles within a refined α-Ti matrix. Microstructural characterization reveals that increasing B4C content (0–1 wt%) induced microstructural hierarchy through dual-phase (α+β) matrix refinement (α-lath reduction: 7.79 → 6.89 μm) and reinforcement architecture optimization, achieving 96.2 % high-angle grain boundaries and ceramic network continuity. The heterostructure facilitates synergistic deformation mechanisms: TiB + TiC networks facilitate efficient load transfer and dislocation accumulation; preserved α-Ti domains accommodate plastic strain, and Thermal mismatch-induced geometrically necessary dislocations enhance back-stress hardening. Mechanical testing demonstrates superior strength-ductility synergy. The 1 wt% B4C composite achieves a tensile strength of 997.21 MPa (20.97 % vs. Ti matrix) while retaining a uniform elongation of 9.14 %, surpassing conventional trade-offs in particle-reinforced TMCs. Quantitative strengthening analysis reveals synergistic contributions from Hall-Petch refinement, Orowan looping, and solid solution effects, while EBSD-validated strain delocalization mechanisms mitigate early fracture. This work establishes LDED-enabled heterostructuring as a transformative pathway for developing damage-tolerant TMCs, achieving an unprecedented combination of specific strength and damage absorption capacity.